THE IMPACT OF SAVI TEACHING METHODOLOGY ON STUDENTS’ MOTIVATION TO LEARN MATHEMATICS IN SMPN 2 NAN SABARIS CLASS VIII IN THE 2021/2022 ACADEMIC YEAR - Agustin Mayang Sari; Aniswita (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2022)
The lack of student interest in learning mathematics and the continued emphasis on the instructor as the primary source of instruction are the driving forces behind this study. Additionally, learning process is frequently carried out using traditional learning methods. This is evident in the learning process, where many students submit assignments late, students are less interested in learning mathematics because the focus is still on the teacher, and the classroom environment is less than ideal because so many students are still involved in their extracurricular activities. Using a somatic, auditory, visual, and intellectual learning approach is one way to solve this issue. There is a considerable impact of the somatic, auditory, visual, and intellectual learning approaches on students' motivation to learn mathematics in class VIII of SMPN 2 Nan Sabaris Academic Year 2021–2022, according to the study's premise. This research is an experimental research with the research design of The Static Group Comparison Design. The population in this study were all eighth grade students of SMPN 2 Nan ​​Sabaris. The data analysis technique used t-test. Based on the results of data analysis obtained tcount = 2.30 and t-table = 1.67 so that tcount > ttable with a confidence level of 0.05 and a P-value of 0.025. Thus, H1 is accepted and Ho is rejected. It can be concluded that